Kepastian Hukum terhadap Sengketa Kepemilikan Hak Atas Tanah yang Tumpang Tindih (Studi Kasus Putusan Pengadilan Negeri Sengeti Nomor 34/Pdt.G/2017/PN SNT) - Dwinta, Shafira; Nurhadi, Harsanto (Wajah Hukum, 2025)
The occurrence of overlapping ownership of land rights is a legal problem that often occurs in land law. One of the disputes arises from land sale and purchase transactions between individuals that do not have strong evidentiary strength, so it needs to be resolved through litigation. This research is methodized with a statutory approach. It aims to find out how land registration procedures can guarantee rights for holders of land rights and how to resolve the dualism of property rights certificates. This research uses a statutory approach by using secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The author collects data with a qualitative method that makes literature study as a reference in this research. The research data that has been obtained will be analyzed qualitatively. Land registration procedures can guarantee rights for land rights holders by following the rules of PP 24/1997 concerning Land Registration. In the event of dualism of rights ownership, the settlement is through the court to prove the validity of rights ownership based on authentic evidence and witness statements.